3(2x-1)=2(3x-1)

Simple and best practice solution for 3(2x-1)=2(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-1)=2(3x-1) equation:


Simplifying
3(2x + -1) = 2(3x + -1)

Reorder the terms:
3(-1 + 2x) = 2(3x + -1)
(-1 * 3 + 2x * 3) = 2(3x + -1)
(-3 + 6x) = 2(3x + -1)

Reorder the terms:
-3 + 6x = 2(-1 + 3x)
-3 + 6x = (-1 * 2 + 3x * 2)
-3 + 6x = (-2 + 6x)

Add '-6x' to each side of the equation.
-3 + 6x + -6x = -2 + 6x + -6x

Combine like terms: 6x + -6x = 0
-3 + 0 = -2 + 6x + -6x
-3 = -2 + 6x + -6x

Combine like terms: 6x + -6x = 0
-3 = -2 + 0
-3 = -2

Solving
-3 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| s+7y=z | | -10+w-32=36 | | 6x+3(x-2)=16x+8 | | 7y-26=38+9y | | R+38=15 | | 4s-5=1+s | | 6x+8=170 | | -8x-1(-8x+2)=-6 | | -(k+6)=-36+4k | | N^2+5n+7=0 | | X+2x+2+3x+6=170 | | |9-10x|=91 | | xy-3x-3y=0 | | -32+30= | | (3+p)/3-4p=1-(p+7)/2 | | S-46=-16 | | 6x-12=-9 | | -32+34= | | -8(1-2b)-4b=5(2b+2) | | -6(n+1)=-36+4n | | 8p-30=5p | | 27/10-11/4 | | 6.6+1.3x-5.2x=14.4 | | 6+5=-4-6v | | -8(4n-8)=4n-8 | | -8(-5x+2)=264 | | 3(3)(1)4= | | 11x=24+8xsolve | | -4x=2-7x^2 | | x^4+3x^3+3x^2-3x-4=0 | | 2x-18=-4(8x-4) | | 4t-15=4+14 |

Equations solver categories